Simultaneous Detection of Cerebral Metabolism of Different Substrates by in vivo (13)C Isotopomer MRS - Xiang, Yun (2011)
In this report a new method is introduced for simultaneous detection of the metabolism of two (13)C-labeled subtracts in brain in vivo. We recognized and experimentally demonstrated that when a (13)C-labeled substrate generates [1,2-(13)C(2)]acetylCoA ([1-(13)C]acetylCoA) only, glutamate C5, glutamine C5 and apsartate C4 doublets (singlets) are formed exclusively, regardless of the number of turns of the tricarboxylic acid cycle. We utilized the large one-bond (13)C-(13)C homonuclear J coupling between a carboxylic/amide carbon and an aliphatic carbon (~50 Hz) and demonstrated that it is feasible to simultaneously detect the labeling of brain metabolites by two different substrates using different isotopomer signals of the same carbon atom. Uniformly labeled glucose was used to generate the doublets and a second substrate ([2-(13)C] lactate or [1,3-(13)C(2)]β-hydroxybutyrate or [1-(13)C] acetate) was used to generate the singlets. It was shown that contribution to cerebral metabolism from different substrates can be simultaneously measured in vivo.